Evaluation of Self-Confidence in Women with Chronic Disease - Başkan, Sebahat Atalıkoğlu; Tuncer, Sevinç Kose; Güneş, Demet (Makara Journal of Health Research, 2023)
Background: Self-confidence, which is an important emotional need in women, affects women's quality of life. This research was conducted to evaluate the self-confidence of women with chronic diseases. Methods: This study was conducted at the internal medicine clinic of Erzincan Mengücek Gazi Training and Research Hospital in Turkey between August 2019 and June 2020. The sample consisted of 339 female patients with chronic diseases who agreed to participate in this study. Data were collected through face-to-face interviews using information form and the Women’s Self-Confidence Scale. Results: The mean total score of the participants was 136.40 ± 24.92. Scores on the self-confidence scale significantly differed in accordance with the women’s age, body mass index, educational status, type of family, place of residence, number of children, self-care, history of smoking, allocation of time-to-herself, activity, perceived health status, presence of chronic obstructive pulmonary disease and other chronic diseases, and information received about the disease (p < 0.05). Conclusions: Women with chronic diseases had a moderate level of self-esteem. Self-confidence is a person’s belief that they will perform a particular activity successfully and feel valued. People with high self-confidence are likely to be compatible with themselves through accumulating positive thoughts and feelings about themselves. Therefore, increasing the self-confidence of women with chronic diseases is important.